Madrasas Adrift: Examining the Educational Resource Distribution Gap in North Kalimantan's Border Region - Karim (Magister Programme Of Islamic Education Departement at Institut Agama Islam Tarbiyatut Tholabah, 2026)
This article examines the gap between the strategic role of madrasas in the border areas of North Kalimantan and the reality of educational resource distribution. Using a qualitative-descriptive library research method with 53 references (19 national and 34 international sources), this study identifies structural, geographical, managerial, and political factors causing disparities in teacher access, infrastructure, and teaching materials. The findings reveal that madrasas in the border areas experience chronic resource shortages, including a 32% teacher deficit, limited internet and electricity access, inadequate physical facilities, and minimal teaching materials. These conditions negatively impact learning quality, student motivation, and the institutional function of madrasas as moral fortresses and guardians of nationalism. The application of opportunity gap theory (Carter & Welner, 2013) demonstrates that border madrasas lack equitable opportunities compared to urban madrasas. This article offers an affirmative distribution model consisting of four pillars: Madrasah Vulnerability Index, direct block grant mechanism, special teacher incentive packages, and contextual border curriculum. The study recommends policy reforms prioritizing equity over equality in educational resource allocation for madrasas in underdeveloped, frontier, and outermost regions.